2018
DOI: 10.1093/humrep/dey054
|View full text |Cite
|
Sign up to set email alerts
|

Towards an optimal luteal support modality in agonist triggered cycles: a randomized clinical trial

Abstract: 26/6/2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
1
6
0
1
Order By: Relevance
“…Significantly lower implantation rates, CPR, and a higher rate of early pregnancy loss have been documented in antagonist IVF cycles triggered with GnRHa versus hCG despite luteal support with oral E 2 and vaginal progesterone [30]. A randomized controlled trial (RCT) did report similar ongoing pregnancy rates to hCG trigger when patients who were administered GnRHa trigger received low-dose hCG at the time of oocyte retrieval in addition to oral E 2 and intramuscular progesterone [31]. Therefore, our patients may not have received adequate luteal support as only 200 mg of progesterone was prescribed daily.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly lower implantation rates, CPR, and a higher rate of early pregnancy loss have been documented in antagonist IVF cycles triggered with GnRHa versus hCG despite luteal support with oral E 2 and vaginal progesterone [30]. A randomized controlled trial (RCT) did report similar ongoing pregnancy rates to hCG trigger when patients who were administered GnRHa trigger received low-dose hCG at the time of oocyte retrieval in addition to oral E 2 and intramuscular progesterone [31]. Therefore, our patients may not have received adequate luteal support as only 200 mg of progesterone was prescribed daily.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the advantages and disadvantages of LOD and IVM as described above, the currently used GnRH antagonist-based COS is more likely to be chosen as the first-line treatment for PCOS. However, this COS, which consists of using GnRH antagonist for suppression of spontaneous LH surge during gonadotrophin administration and GnRH agonist as a trigger, showed the best clinical outcome except for the occurrence of OHSS in about 10% of the cases [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 98%
“…GnRH antagonist-agonist based COS, which is now widely used for PCOS, seems to be the best COS for PCOS even though it is accompanied with OHSS in up to 12% of all cases [1][2][3][4][5] . However, almost all of the studies on this topic reported the incidence of moderate to severe OHSS.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the rate of considerable OHSS in the agonist trigger group, although significantly lower than in the hCG trigger group, was surprisingly high (5%). It is likely that the exceptionally high rate of OHSS among IVF patients triggered with a GnRH agonist trigger in the study by Elgindy et al (16) stems from the addition of hCG on the day of OPU as well as from the fact that all these patients underwent embryo transfer and therefore fetal hCG may have contributed to the higher rates of late OHSS. In contrast, a small retrospective study by Safrai et al (17) reported similar OPR and LBR and no OHSS following MVP or oral dydrogesterone LPS in GnRH triggered cycles.…”
Section: Lps Following Gnrh Agonist Triggermentioning
confidence: 99%